Crosstalk between foetal vasoactive peptide hormones and placental aminopeptidases regulates placental blood flow: Its significance in preeclampsia. (April 2022) - Yoshihara, Masato; Mizutani, Shigehiko; Matsumoto, Kunio; Kato, Yukio; Masuo, Yusuke; Tano, Sho; Mizutani, Hidesuke; Kotani, Tomomi; Mizutani, Eita; Shibata, Kiyosumi; Kajiyama, Hiroaki
Abstract: In pregnancy, placental circulation occurs through two independent circulation systems: foetoplacental and uterine (spiral artery)-placental lake. Crosstalk between the foetal peptide hormones, angiotensin II (A-II) and vasopressin (AVP), and their degrading placental aminopeptidases (APs), aminopeptidase A for A-II and placental leucine aminopeptidase for both AVP and oxytocin, primarily regulate placental circulation. On the other hand, placental circulation represents an arteriovenous shunt. In normal pregnancy, the blood pressure decreases, despite increased cardiac output and plasma volume, probably due to the arteriovenous shunt in the growing placenta. Actually, the foetal vasoactive hormones in the foetoplacental circulation are much higher than those in the maternal circulation throughout pregnancy. In normal pregnancy, AP activity derived from the placenta in maternal blood increases with gestation and placental growth. Foetal hypoxia increases the secretion of foetal both AVP and A-II. Although there is an increase in both AP activities in the maternal blood in normal pregnancy, their activities increase more than those in normal pregnancy during mild preeclampsia. However, both AP activities decline significantly compared than those in severe preeclampsia. This suggests that AP prevents leakage of increased foetal vasoactive hormones into the maternal blood in mild preeclampsia, and its protective role breaks down in severe preeclampsia, leading to a massive leak of the hormones into maternal circulation and consequent marked contraction of both the maternal vessels and the uterus. Consequently, AP activity in both placenta and maternal blood acts as the foeto-maternal barrier for foetal vasoactive hormones and thus contributes to the onset of preeclampsia. Highlights: The placental APs can be potential therapeutic biologics for treating severe preeclampsia. AP activity in both placenta and maternal blood acts as the foeto-maternal barrier for foetal vasoactive hormones . The potential therapeutic application of recombinant APs might serve as pharmaceutical agents for preeclampsia.